Effect of Spindle Speed of Bar-Plate Rotary Friction Welding Machine on Joint Interface Area and Hardness Value - Michael Simorangkir; Yohanes Yohanes; Muftil Badri (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2023)
This study aims to determine the effect of the rotational speed parameter on the joint interface weld area and the value of hardness on similar materials. Welding parameters used the rotational speed of 2,484 rpm, 2,613 rpm and 4,335 rpm. Test method used in this research was liquid penetrant, macro and micro-observation and hardness test. The results of the liquid penetrant test showed no defects on the surface of the connection. In macro-observation, where there is a fairly large void at rotational speed of 2,484 rpm, which has length is 2,69 mm, then shrinks at 2,613 rpm to 1,52 mm, then at 4,335 rpm there is no visible void. In micro-observations showed that the weld metal area had a finer grain structure than the HAZ (Heat Affected Zone) and base metal areas this affect hardness value. The results of the hardness test are that the higher the rotational speed the higher the hardness value produced.